Time, Typology, and Point Traditions in North Carolina Archaeology : Formative Cultures Reconsidered - Daniel, I. Randolph (Book collections on Project MUSE., 2021)
"A reconsideration of the projectile point typology originally set out in the landmark publication The Formative Cultures of the Carolina Piedmont by Joffre Coe in 1964"--